Diabetic macular ischaemia is associated with narrower retinal arterioles in patients with type 2 diabetes. (February 2015) - Liew, Gerald; Sim, Dawn A.; Keane, Pearse A.; Tan, Ava G.; Mitchell, Paul; Wang, Jie Jin; Wong, Tien Y.; Fruttiger, Marcus; Tufail, Adnan; Egan, Catherine A.
Abstract Purpose Diabetic macular ischaemia (DMI) is an important cause of visual loss in patients with diabetes, but its relationship to the larger retinal vessels is unknown. We examined whether retinal vessel calibre is related to DMI. Methods Clinic‐based case–control study of patients with type 2 diabetes. The presence and severity of DMI was assessed using Early Treatment Diabetic Retinopathy Study (ETDRS) protocols from fundus fluorescein angiographic (FFA) images. Custom software was used to quantify the greatest linear dimension and area of the foveal avascular zone (FAZ). Retinal vessel calibre was measured using a semi‐automated software on fundus fluorescein images. Results Of 53 patients examined, 18 (34%), 18 (34%) and 17 (32%) had no/mild, moderate and severe DMI, respectively. Persons with moderate or severe DMI had narrower mean retinal arteriolar calibre than persons with no/mild DMI (140.6 μm 95% confidence interval (CI) 134.7, 146.4 versus 150.7 μm, 95% CI 142.5, 158, p = 0.04). The association remained after multivariate adjustment for age, gender, previous panretinal photocoagulation, neovascularization at the disc and elsewhere and diabetic retinopathy severity. Increased FAZ size was also associated with narrower arteriolar calibre. Retinal venular calibre and arteriole to venule ratio (AVR) were not associated with DMI. Conclusions Retinal arteriolar narrowing was associated with moderate‐to‐severe macular ischaemia in eyes with diabetic retinopathy. This suggests that larger vessels other than capillaries may also be associated with DMI.